Framework for the documentation of nature-based solutions for stormwater management - Gema Sakti Raspati; Stian Bruaset; Kamal Azrague; Rita Maria Ugarelli; Tone Merete Muthanna; Berit Time; Edvard Sivertsen (Blue-Green Systems, 2023)
Nature-based solutions (NBSs) are widely implemented for stormwater management; as such they have become important assets that require proper asset management at different stages of their service life. Hence, there is a need for systematic documentation of the applied NBS in accordance with the principles of infrastructure asset management and in combination with a set of requirements in the newly adopted National Standard NS3456:2022 in Norway. A framework for the documentation of NBSs was developed based on a systematic literature study, the experience gained from operating NBS pilots, and the interaction with stakeholders in a research centre, Klima 2050. The framework proposed a set of specific information in the form of a data structure covering a set of categories that presents information gathered during the planning, design, operation, and maintenance phases of the NBS. Both technical and sociotechnical aspects were included in the data structure. The data structure can be tailor-made depending on the type of NBS applied. The data structure was applied in documenting the NBS pilots of the research centre to demonstrate the framework's ability to help ensure a smooth flow of information from the actors involved in the planning, constructing, and operating of the NBS. HIGHLIGHTS Application of infrastructure asset management principles in the implementation of NBS for stormwater management.; Systematization of the data requirement for NBS planning, design, construction, and operation and maintenance based on literature and pilot studies.; Formulation of a framework for documentation of NBSs.; Suggestion for a data structure with an example of implementation in an NBS pilot.;